Efektivitas Platform Smart Campus dalam Mendukung Pembelajaran Berbasis Proyek: The Effectiveness of the Smart Campus Platform in Supporting Project-Based Learning - Sadrina Sadrina; Septi Indah Permatasari; Anita Wijaya; Yunia Antantri Subekti (ITScience (Information Technology and Science), 2026)
Digital transformation in higher education has led to the emergence of the smart campus concept as a solution to create a learning environment that is smart, efficient, and data-driven. The implementation of a smart campus is highly relevant for vocational education, including maritime polytechnics, because it supports the integration of theory, practice, and industry experience. At Malahayati Maritime Polytechnic (Poltekpel), integrating digital technology through a smart campus platform is expected to enhance the effectiveness of project-based learning and strengthen industry collaboration. This study aims to analyze the effectiveness of smart campus implementation in supporting maritime vocational learning and industrial collaboration, thereby serving as a reference for improving the quality of digital-based education in maritime polytechnics. This quantitative study assessed the effectiveness of the smart campus at the Malahayati Maritime Polytechnic. Based on data from 300 respondents, the results showed that the smart campus effectively supports project learning and industrial collaboration, with digital literacy significantly influencing its effectiveness. This study assessed the effectiveness of the smart campus platform at the Malahayati Maritime Polytechnic. Of the 300 respondents, the platform was considered effective, especially for ease of access and data integration, but industrial collaboration remained low. Digital literacy significantly influenced the effectiveness of platform use (r = 0.712; R² = 0.506). Overall, the smart campus is performing well but needs improvement in its industry collaboration. The smart campus is considered effective at supporting project-based learning, but industry integration remains lacking. Digital literacy plays a significant role in the effective use. The system is working well, but needs improvement in industry collaboration and digital capabilities.